PENGARUH STRUKTUR MODAL, LIKUIDITAS, LEVERAGE DAN PROFITABILITAS TERHADAP KEBIJAKAN DEVIDEN PADA PERUSAHAAN DI BURSA EFEK INDONESIA - suwanda, ari; Purba, Mortigor Afrizal (LPPM Universitas Putera Batam, 2021)
The decision to determine the right dividend policy is to create effectiveness in financial management. This study aims to determine the impact of certain variables, namely capital structure, liquidity, leverage and profitability on dividends in companies on the Indonesia Stock Exchange. The population is 26 companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2015-2019. The sampling technique in this study used a purposive sampling method so that 8 listed companies met the criteria in selecting the sample. The data used in this study are secondary data in the form of financial reports obtained from the Indonesia Stock Exchange. The results of the F test produce a significant effect, which means that the capital structure, liquidity, leverage and profitability simultaneously affect dividends so that the regression model in this study is suitable for research. Partially, the t-test shows that the capital structure, liquidity and leverage significantly affect dividends policy, while profitability does not have a significant effect on company dividends policy.